2015
DOI: 10.1080/10550887.2015.1059225
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Medical Maintenance: An Early 21st-Century Perspective

Abstract: Methadone medical maintenance is the treatment of stable methadone-maintained patients in primary care physicians' offices under an exemption from federal methadone regulations. Reports from seven such programs in six states show high retention and low frequencies of illicit drug use. Patients and physicians indicate high levels of satisfaction. Although methadone maintenance has a long history of safety and efficacy, most methadone medical maintenance programs are no longer operating or accepting new patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 48 publications
0
22
0
4
Order By: Relevance
“…Elevated retention rates with a noteworthy decrease of illicit opiate use have been observed under methadone maintenance treatment [24][25][26][27]. In addition, there are reductions of other associated problems such as intravenous drug use, crime [28][29][30], and improvement of social functioning [31]. Later studies reported that prolonged methadone maintenance normalized the immune system function in heroin addicts [32], as well as the altered stress response [33].…”
Section: Methadonementioning
confidence: 99%
“…Elevated retention rates with a noteworthy decrease of illicit opiate use have been observed under methadone maintenance treatment [24][25][26][27]. In addition, there are reductions of other associated problems such as intravenous drug use, crime [28][29][30], and improvement of social functioning [31]. Later studies reported that prolonged methadone maintenance normalized the immune system function in heroin addicts [32], as well as the altered stress response [33].…”
Section: Methadonementioning
confidence: 99%
“…These are methadone or buprenorphine / naloxone, taken on a daily basis. Methadone is a selective and long-lasting μ-agonist (although it also functions as an NMDA antagonist), whereas buprenorphine is a μ-partial agonist that also has κ-antagonist or partial agonist effects [23,83,84]. The antagonist naloxone is added to this buprenorphine formulation, as an abuse deterrent (i.e., to avoid diversion and injection).…”
Section: Existing Treatmentsmentioning
confidence: 99%
“…The antagonist naloxone is added to this buprenorphine formulation, as an abuse deterrent (i.e., to avoid diversion and injection). There are extensive long-term data showing considerable therapeutic benefit of chronic methadone and buprenorphine / naloxone maintenance, when used in high quality programs, providing sufficient doses of these medications [84,85]. …”
Section: Existing Treatmentsmentioning
confidence: 99%
“…In 1990, there was zero HIV antibody presence in another study involving an office-based pilot program of methadone maintenance [30]. In addition to harm reduction, there are also improvements in employment and in social functioning among methadone-maintained patients [5,6,26,31].…”
Section: Methadone Maintenance Effectivenessmentioning
confidence: 99%